2019
DOI: 10.1556/650.2019.31390
|View full text |Cite
|
Sign up to set email alerts
|

Extracranialis carotis aneurysmák korszerű kezelése

Abstract: Introduction: Aneurysm of the extracranial carotid artery is a rare condition and there is a diversity in the etiology. The proper treatment could be a real challenge for the surgeons. Aim: Analysis of perioperative and long term results of invasive treatment for carotid artery aneurysm. Method: A retrospective review was conducted of patients who had open or endovascular surgery due to carotid artery aneurysm through the last 13 years at the Department of Vascular Surgery of the Semmelweis University and at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 24 publications
0
4
0
1
Order By: Relevance
“…The most important problem in endovascular procedures is that the rate of reprocessing such as re-stenosis is higher than surgical operations. 12,13 Endovascular therapies should be recommended to patients when there is no healthy ICA other than the extracranial aneurysm or there is not enough ICA length to be taken under control. Treatment modality of carotid artery aneurysm has largely evolved from operative to endovascular intervention at many institutions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The most important problem in endovascular procedures is that the rate of reprocessing such as re-stenosis is higher than surgical operations. 12,13 Endovascular therapies should be recommended to patients when there is no healthy ICA other than the extracranial aneurysm or there is not enough ICA length to be taken under control. Treatment modality of carotid artery aneurysm has largely evolved from operative to endovascular intervention at many institutions.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding both forms of treatment, the decisive factors are risk of cranial nerve damage, re-intervention necessity, mortality, length of hospital stay, and frequency of cerebrovascular events. 3,12,13 Various studies have shown that surgical treatment is one of the effective treatment methods in carotid aneurysms. 1,8,13 The localization, etiology, clinical development and operative approaches of the lesions were investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A carotis sebészetébenamely szakmánk folyamatosan reflektorfényben lévő területe -1996- tól a legjobb hosszú távú eredményeket biztosító technikát az eversios endarterectomiát alkalmazzuk. 2018-tól a perioperatív morbiditás csökkentése és a betegbiztonság fokozása céljából meghonosítottuk a direkt neuromonitoringot lehetővé tevő lokoregionalis anaesthesiát [72][73][74].…”
Section: -Ban Az Osztály Működését Az Európai Mellkassebészunclassified
“… 1 The most common underlying causes related to these true aneurysms include atherosclerosis, trauma, fibromuscular dysplasia, infection, connective tissue disorders, and large vessel vasculitis. 2 EICA generally has no obvious clinical symptoms. Some patients usually show pain, throbbing masses or cranial nerve palsy.…”
Section: Introductionmentioning
confidence: 99%